Analisis Faktor Determinan yang Mempengaruhi Pembiayaan Bermasalah pada Bank Umum Syariah di Indonesia - Sarah Nurfadilah (COMPETITIVE, 2022)
This study aims to analyze the determinants that affect problematic financing in Islamic Banks in Indonesia. The data analysis method used is Multiple Regression Analysis. The reseach data consists of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Operating Effeciency Ratio (BOPO), and Non Performing Financing (NPF). The results showed thats the Capital Adequacy Ratio (CAR) and the Financing to Deposit Ratio (FDR) had a negative and significant effect on Non Performing Financing (NPF). Operating Effeciency Ratio (BOPO) has a positive and significant effect on Non Performing Finance. The Results showed that the variables CAR, FDR, and BOPO simultaneously affect the NPF of Islamic Banks in Indonesia.